Social Media Analytics: Instagram Utilization for Delivering Health Education Messages to Young Adult in Indonesia - Odilia Firsti Wida Mukti; Nuzulul Kusuma Putri (Universitas Airlangga, 2021)
Background: Social media marketing has become one of the most widely used forms of digital marketing in social marketing. Organizations that drive change in young people, such as the Center for Indonesia's Strategic Development Initiatives (CISDI), rely heavily on social media marketing in communicating various health issues to the public. However, only a few studies have used social media related data to understand the effectiveness of this media in the delivery of health issues. Objective: This study aims to analyze the utilization of social media marketing conducted by CISDI for delivering health messages and its impact to young adult in Indonesia using social media analytics. Methods: Real-time data were obtained through Keyhole as a social media analytics tool and audience insight of online and offline classes used for social analytic in this study. This research monitored the use of CISDI’s social media by using audience metrics and individual post metrics collected from April 2019 to April 2020. Online and offline class audience data were obtained from the CISDI engagement database which was used as a complement to audience metrics information. Analysis of metrics was used to describe the audience that had been reached by the Center for Indonesia's Strategic Development Initiatives, how health messages could engage with the groups of audience, and how social media marketing can move the audience. Results: The result of this study shows that social media utilization for delivering health messages brought impact on audience participation. Currently trending issues, such as sex education (average engagement rate = 14,43%). By promoting through social media, CISDI has engaged 10266 audience to participate in their classes. Conclusion: Social media utilization benefit CISDI in engaging audience and move them to participate in their cause.